2018
DOI: 10.1556/168.2018.19.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Viral metacommunities associated to bats and rodents at different spatial scales

Abstract: One of the main goals of community ecology is to measure the relative importance of environmental filters to understand patterns of species distribution at different temporal and spatial scales. Likewise, the identification of factors that shape symbiont metacommunity structures is important in disease ecology because resulting structures drive disease transmission. We tested the hypothesis that distributions of virus species and viral families from rodents and bats are defined by shared responses to host phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Considering that some species are reservoirs of numerous viruses, some of which have large impacts on human health, studies on viral diversity in rodents have recently increased [3,9,[84][85][86]. Hence, 173 viral species belonging to more than 65 genera have been described in rodents to date, among which 53 are zoonotic, such as mammarenaviruses and hantaviruses [30,87]. However, few studies have explored the links among viral diversity, host ecology, and habitats [8,88,89].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that some species are reservoirs of numerous viruses, some of which have large impacts on human health, studies on viral diversity in rodents have recently increased [3,9,[84][85][86]. Hence, 173 viral species belonging to more than 65 genera have been described in rodents to date, among which 53 are zoonotic, such as mammarenaviruses and hantaviruses [30,87]. However, few studies have explored the links among viral diversity, host ecology, and habitats [8,88,89].…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to results found by Luis et al () when building viral association networks in Rodentia and Chiroptera, who then used the centrality metrics as a response variable in a generalized linear model to determine the phylogenetic, functional and ecological characteristics that are responsible for this high connectivity in bats. This pattern of higher host diversity among bat viruses than rodent viruses has been observed in viral metacommunities using analyses at different spatial scales (Nieto‐Rabiela, Suzán, Wiratsudakul, & Rico‐Chávez, ), and it has been suggested that this is due to their higher dispersal ability compared with rodents (Wang, Walker, & Poon, ). However, since studies on viruses detected in others mammals have not yet been carried out at a similarly large scale, it is not clear whether bats' level of host–virus connectivity is atypically high among mammals; we can only conclude that it is higher than in rodents.…”
Section: Discussionmentioning
confidence: 52%
“…Exploratory surveys indicate that the diversity and composition of virus assemblages differ among rodent host species [20,21,23,29]. Consistent with this, broad comparative assessments indicate that viral diversity and assemblage structure reflect rodent host phylogeny [30,31], with associations contingent on spatial scale [30]. Some evidence suggests that diversity also relates to ecological factors like host range size and sympatry [31], highlighting the potential for cross-species transmission to influence viral assemblage structure.…”
Section: Introductionmentioning
confidence: 74%